Is Taurolidine-citrate an effective and cost-effective hemodialysis catheter lock solution? A systematic review and cost- effectiveness analysis - Kavosi, Zahra (Med J Islam Repub Iran, 2016)
Background: Prevention of catheter-related infection is of prime importance,. However, because of the risks caused by the leakage of circulating antibiotics and development of resistance to antibiotics, they are replaced by lock solutions. The aim of this study was to evaluate the efficacy and cost- effectiveness of taurolidine-citrate as a hemodialysis catheter lock solution compared to other common alternatives in Iran. Methods: To evaluate the efficacy of taurolidine-citrate, a systematic review was conducted by searching electronic databases. The outcomes of interest for cost-effectiveness analysis were as follows: "Catheter-related bacteremia episodes"; "catheter-related bacteremia-free survival"; "catheter thrombosis rate" for efficacy evaluation and "reduction of catheter-related infection". For evidence synthesis, a meta-analysis was conducted on the extracted efficacy data. To evaluate the cost of treatments, direct medical costs were included, and the incremental cost-effectiveness ratio was calculated for each comparison. The payers’ (patients and insurance companies) perspectives were used for cost analysis. Results: After carrying out the systematic process, three articles were included in the analysis. Considering 95% confidence interval, the relative difference was -0.16 (-0.25 to -0.07) for catheterrelated bacteremia episode, indicating that the rate of catheter-related infections in hemodialysis patients who used taurolidine-citrate was 16% less than in those hemodialysis patients who received heparin. Considering 95% confidence interval, the relative difference was 0.13 (-0.06 0.32) for catheter thrombosis, showing that the rate of catheter-related thrombosis in hemodialysis patients who used taurolidine-citrate was 13% more than in hemodialysis patients who received heparin. The results of this analysis indicated that taurolidine-citrate, compared to heparin, was more effective in preventing catheter-related infection; therefore, it could be considered as a superior strategy. Nevertheless, compared to heparin-gentamicin combination, taurolidine-citrate is an inferior strategy because of its higher cost and lower infection prevention. Conclusion: Compared to heparin, taurolidine-citrate is a superior option, but it is an inferior strategy compared to heparin-gentamicin combination. The clinical evidences on taurolidine-citrate, heparin and gentamicin/heparin are not sufficient for making confident decisions.